Social support and symptoms of antenatal depression among women screened for gestational diabetes mellitus: A cross-sectional study in Northern Vietnam (the VALID II study). - Ai T Nguyen; Kien Dang Nguyen; Hieu Minh Le; Thanh D Nguyen; Dan W Meyrowitsch; Ib C Bygbjerg; Jens Søndergaard; Hanh T T Nguyen; Christina A Vinter; Ditte S Linde; Tine M Gammeltoft; Vibeke Rasch (PLoS ONE)
Objectives This study from Northern Vietnam aims to assess the association between social support and symptoms of depression among pregnant women screened for gestational diabetes mellitus (GDM). Methods A cross-sectional study was conducted among 823 pregnant women in Thai Binh, Vietnam. The women were screened for GDM and structured questionnaire were used to collect data on social support factors, GDM factors, and symptoms of depression. The diagnosis of GDM was based on the 2-hour 75-g OGTT according to WHO 2013 criteria. The Edinburg Postpartum Depression Scale (EPDS) with a cut-off of 10 and the Multidimensional Perceived Social Support Scale (MSPSS) were used to assess depression symptoms and perceived social support, respectively. Logistic regression analysis was conducted to measure the associations between social support, GDM-related factors, and symptoms of depression. The relationship between social support score and symptoms of depression was evaluated using Spearman's correlation. The strength of the associations were measured by adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results The prevalence rates of GDM and symptoms of depression were 22.2% (95%CI: 19.4-25.2) and 23.0% (95%CI: 20.1-26.0), respectively. Women who had moved away from their commune of birth and women who reported another person than their husband to be the primary person to confide in had increased odds of depression (aOR = 1.74; 95%CI:1.19-2.56 and aOR = 2.36; 95%CI:1.48-3.75, respectively). A reported lack of social support was strongly associated with increased odds of depression symptoms among both women with gestational diabetes mellitus (aOR = 6.16, 95% CI:2.35-16.12) and without gestational diabetes mellitus (aOR = 2.81; 95%CI: 1.67-4.75). When analysing the correlation between social support and depression symptoms, a negative correlation was found, with decreasing depression scores as the social support score increased. Conclusion The prevalence of symptoms of depression was high in our study, and women in Northern Vietnam who feel well-supported socially are less likely to report symptoms of depression. This finding applies both to women with and without GDM.